Predicting Health Behavior Using the Theory of Planned Behavior: Lessons Learned from the COVID-19 Pandemic - Winarno, Alphonsus Rachmad Djati; Adiwena, Bartolomeus Yofana (Gadjah Mada Journal of Psychology (GamaJoP), 2025)
Clean and healthy living behavior (CHLB) is one of the fundamental aspects of life. However, public awareness of health behaviors in Indonesia is still relatively low. This research aimed to predict health behaviors using the Theory of Planned Behavior (TPB) framework, which has the components of attitude, subjective norms, behavioral control, behavioral intention, and behavior, in the context of the COVID-19 pandemic. An incidental sampling technique was used to select 118 participants aged 20-40. Data were collected online using 17 questions about TPB. Path analysis showed that attitude and behavioral control predict health behavior indirectly through behavioral intention (partial mediation). On the other hand, subjective norms do not significantly predict intention but are directly related to health behavior. The implications of this study for policy and public health are discussed further.